Evaluation of Reliability of Visual Field Examination in Glaucoma Patients - Asad Raza Jafri, Atiya Rahman, Uzma Fasih, Arshad Shaikh, Nisar Shaikh, M. S Fehmi (Pakistan Journal of Ophthalmology, 2009)
Purpose: The purpose of our study was to evaluate the reliability of visual field examination in glaucoma patients undergoing perimetery for the first time on Octopus 300 series perimeter. Materials and Methods: The study was conducted in the Department of Ophthalmology, Abbasi Shaheed Hospital from January 2007-June 2008. Patients were randomly selected from the glaucoma clinic who went for routine perimetery for the first time. Patients were examined in detail, diagnosis was established and were sent for field examination to assess the extent of damage by glaucoma .Perimetery was done on Octopus 301 series perimeter after setting all the parameters and under constant supervision. Results: A total of 117 patients were examined from January 2007- June 2008. A male preponderance was seen and majority of the patients belonged to 60-70 years age group making upto 37.4 %followed by 40-50 years age group i.e 25.6%. Maximum number of patients have percentage of false positives and false negatives between the range of 0-5 % which shows that a large number of patients(62% patients in false positives and 79% patients in false negatives in their right eyes and 68.4% patients in false positives and 74.6% patients in false negatives in their left eyes) had a reliable field96(82%) patients had Reliability factor in acceptable normal range their right eyes and 104(89%) patients had reliability factor in acceptable normal range in left eyes. It shows that majority of patients had a reliable field test. It is also obvious that fields of left eyes were more reliable as compared to right eyes. Conclusion: It was concluded that computerized perimetery could play an important role to diagnose and assess the progression of glaucoma provided its reliability lies within the indices set by the manufacturers of the perimeter. To make this test reliable one needs full cooperation and comfortable seating of the patient, better understanding of the test and accurate setting of the parameters of the machine so that there is less chance of false positive and false negative catch trials and reliability factor remains within normal limits.